Seasonal Variations in Phytochemical Parameters of Withania coagulans - Gehlot, Meenu; Kasera, Pawan K; Hussain, Shahdab (Annals of Arid Zone, 2016)
The present paper deals with seasonal variations in leaf pigments, proline, total sugars, crude protein and phosphorus contents in the leaves of Withania coagulans. Results revealed that maximum amount of total chlorophylls, carotenoids and crude protein were observed during the rainy season. However, maximum concentrations of total sugars and proline were recorded in winter, while phosphorus was maximum in summer season. Key words: Withania coagulans, leaf pigments, proline, total sugars, crude protein, phosphorus.